Heterologous ORFV–Ad26 vaccination broadens antibody breadth and amplifies cellular immunity against SARS-CoV-2 spike - Reguzova, Alena; Haug, Verena; Müller, Melanie; Fandrich, Madeleine; Dulovic, Alex; Amann, Ralf (Frontiers in Immunology, 2025)
The durability of vaccine-induced immunity is often limited by waning responses, antigenic drift, and anti-vector immunity, highlighting the need for innovative vaccination strategies. Heterologous prime–boost approaches can help overcome these barriers by exploiting the complementary strengths of distinct platforms. Here, we evaluated a replication-deficient Orf virus-based spike vaccine (ORFV-S) in combination with the licensed Ad26 vector vaccine Jcovden (Ad26.COV2.S), using SARS-CoV-2 model. In a clinically aligned intramuscular immunogenicity screen in mice, Jcovden induced strong early anti-spike antibody responses but showed limited boostability, whereas ORFV-S was highly boost-responsive. Mixed regimens outperformed both homologous schedules. ORFV-S prime followed by Jcovden boost elicited the highest spike-binding antibody titers and vigorous CD4+ and CD8+ T-cell responses with a dominant Th1 profile. In the reverse regimen, ORFV-S boost improved inhibition across multiple SARS-CoV-2 variants, including immune-evasive strains and indicated qualitative improvements in the response breadth. Together, these findings suggest that sequence-dependent effects allow heterologous schedules to emphasize either cellular or humoral arms of the adaptive response.